2005
DOI: 10.1080/01443610500060768
|View full text |Cite
|
Sign up to set email alerts
|

Trends in uterine rupture in Enugu, Nigeria

Abstract: Our objective was to determine the trend of rupture of the gravid uterus at Enugu, Nigeria and to determine any change in pattern of presentation, management and outcome of such patients. The birth register of 4,333 deliveries at the University of Nigeria Teaching Hospital Enugu from January 1997 and December 2000 were reviewed. Forty-one cases of ruptured uterus were identified and analysed. The incidence of uterine rupture was 1 in 106 deliveries with a mean maternal age of 31.2 years. The majority (75.6%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 2 publications
5
27
0
Order By: Relevance
“…Two studies from Nigeria reported on uterine rupture. In the first study, 21% of patients had no uterine scar, and prolonged labour and grand multiparity were associated with the rupture [27]. The incidence of uterine rupture in this study was 1 in 106 births (=9.4/1,000).…”
Section: Aetiologymentioning
confidence: 43%
“…Two studies from Nigeria reported on uterine rupture. In the first study, 21% of patients had no uterine scar, and prolonged labour and grand multiparity were associated with the rupture [27]. The incidence of uterine rupture in this study was 1 in 106 births (=9.4/1,000).…”
Section: Aetiologymentioning
confidence: 43%
“…5 Rupture of the gravid uterus is an obstetric catastrophe mostly domiciled in developing countries of the world especially in sub-Saharan Africa. 1,[10][11][12][13][14][15] This model is targeted at ruptured uterus because it is beginning to emerge as a common cause of maternal and perinatal mortality in our environment. 1 Obstructed labour is a major cause of maternal mortality and a common cause of ruptured uterus from previous literatures.…”
Section: -4mentioning
confidence: 99%
“…17 However, the trends have begun to change especially in this part of the world where traditional/unskilled birth attendants are carrying out a lot of unconventional birth practices (abdominal massage) predisposing parturients to ruptured uterus. [11][12][13][14][15] In addition, previously, ruptured uterus was associated with women of high parity in contrast to the current trends in which ruptured uterus is also seen amongst women of low parity. 1,[11][12][13][14][15]19 Looking at these emerging problems in our society what are the most likely causes?These include social/cultural factors, ignorance, religious factors, economic factors and poor infrastructure/transportation.…”
Section: -4mentioning
confidence: 99%
See 2 more Smart Citations